IMPLEMENTASI PEMBELAJARAN BERBASIS HYBRID LEARNING PADA PENDIDIKAN AGAMA ISLAM DI MASA PANDEMI (STUDI KASUS SMP KEMALA BHAYANGKARI 1 SURABAYA) - imam muslim (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
During the pandemic, most of the learning is done online and some uses hybrid learning. Therefore, an effective learning method is needed, where students are able to learn well and the teacher is able to convey the material well as well. This study aims to determine the implementation of hybrid learning-based learning in Islamic religious education at SMP Kemala Bhayangkari 1 Surabaya during the pandemic. The method used in this research is descriptive with a qualitative approach. The results of interviews conducted with various parties stated that schools in coordination with various parties must provide good preparation so that there is no unpreparedness of a teacher, student, infrastructure, and material. This is so that learning runs more efficiently and health is also maintained. Keywords: learning, hybrid learning. Keyword: learning, hybrid learning